Manajemen Sarana dan Prasarana di Era Disrupsi Sebagai Pendukung Proses Pembelajaran Pasca Pandemi Covid-19 - Afiful Ikhwan; Sri Nurul Qomariyah (JIE (Journal of Islamic Education), 2022)
In this era of globalization, education is increasingly becoming a primary need that cannot be denied the existence of its importance to assess an individual's quality. Many educational institutions are competing to improve their quality so that parents are interested in sending their sons and daughters there, such as facilities and new flagship programs that do not yet exist in other schools as infrastructure to support the learning process. The study in this paper focuses on the infrastructure management process as a supporter of the learning process at SD Muhammadiyah Inovatif Ponorogo. This study uses a qualitative descriptive approach, data collection techniques from structured interviews, document analysis and observation, data analysis techniques using Miles & Huberman theory with coding, finding themes and categorized. They check the validity of the data using triangulation; credibility, transferability, dependability and confirmability. The results of the study show that: (a) quality facilities and infrastructure will improve the quality of students in both academic and non-academic fields; (b) Management of facilities and infrastructure is carried out by planning, procuring, using, maintaining, inventorying, and eliminating school infrastructure; (c) The emphasis on infrastructure management at SD Muhammadiyah Inovatif Mlarak Ponorogo focuses on efforts to support online learning by teachers by upgrading the internet, personal computers (PC), laptops and mobile phones.